Adjuvant and Neoadjuvant Treatment of Triple-Negative Breast Cancer With Chemotherapy. Issue 1 (January 2021) - Marra, Antonio; Curigliano, Giuseppe
Abstract : Abstract: Triple-negative breast cancer (TNBC) accounts for 15% to 20% of all invasive breast carcinomas and is defined by the lack of estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2. Although TNBC is characterized by high rates of disease recurrence and worse survival, it is significantly more sensitive to chemotherapy as compared with other breast cancer subtypes. Accordingly, despite great efforts in the genomic characterization of TNBC, chemotherapy still represents the cornerstone of treatment. For the majority of patients with early-stage TNBC, sequential anthracycline- and taxane-based neoadjuvant chemotherapy (NACT) represents the standard therapeutic approach, with pathological complete response that strongly correlates with long-term survival outcomes. However, some issues about the optimal neoadjuvant regimen, as well as the effective role of chemotherapy in patients with residual disease after NACT, are still debated. Herein, we will review the current evidences that guide the use of (neo)adjuvant chemotherapy in patients with early-stage TNBC. Furthermore, we will discuss current controversies, including the incorporation of platinum compounds to the neoadjuvant backbone and the optimal treatment for patients with residual disease after NACT. Lastly, we will outline potential future directions that can guide treatment escalation and de-escalation, as well as the development of new therapies. In our view, the application of multi-omics technologies, liquid biopsy assays, and machine learning algorithms are strongly warranted to pave the way toward personalized anticancer treatment for early-stage TNBC.